A history of platform mound ceremonialism - Kassabaum, Megan C. (Gainesville)
xv, 250 sayfa
Keywords: “This book presents a temporally and geographically broad yet detailed history of an important form of Native American architecture, the platform mound, revealing unexpected continuities in moundbuilding over many thousands of years.“ --